Soluble endoglin regulates expression of angiogenesis-related proteins and induction of arteriovenous malformations in a mouse model of hereditary hemorrhagic telangiectasia - Gallardo-Vara, Eunate (Dis Model Mech, 2018)
Endoglin is a transmembrane glycoprotein expressed in vascular endothelium that plays a key role in angiogenesis. Mutations in the endoglin gene (ENG) cause hereditary hemorrhagic telangiectasia type 1 (HHT1), characterized by arteriovenous malformations (AVMs) in different organs. These vascular lesions derive from abnormal processes of angiogenesis, whereby aberrant vascular remodeling leads to focal loss of capillaries. Current treatments for HHT1 include antiangiogenic therapies. Interestingly, a circulating form of endoglin (also known as soluble endoglin, sEng), proteolytically released from the membrane-bound protein and displaying antiangiogenic activity, has been described in several endothelial-related pathological conditions. Using human and mouse endothelial cells, we find that sEng downregulates several pro-angiogenic and pro-migratory proteins involved in angiogenesis. However, this effect is much reduced in endothelial cells that lack endogenous transmembrane endoglin, suggesting that the antiangiogenic activity of sEng is dependent on the presence of endogenous transmembrane endoglin protein. In fact, sEng partially restores the phenotype of endoglin-silenced endothelial cells to that of normal endothelial cells. Moreover, using an established neonatal retinal model of HHT1 with depleted endoglin in the vascular endothelium, sEng treatment decreases the number of AVMs and has a normalizing effect on the vascular phenotype with respect to vessel branching, vascular density and migration of the vascular plexus towards the retinal periphery. Taken together, these data show that circulating sEng can influence vascular development and AVMs by modulating angiogenesis, and that its effect on endothelial cells depends on the expression of endogenous endoglin. This article has an associated First Person interview with the first author of the paper.